2017
DOI: 10.1002/2016ja023811
|View full text |Cite
|
Sign up to set email alerts
|

The theoretical foundation of 3‐D Alfvén resonances: Time‐dependent solutions

Abstract: We present results from a 3‐D numerical simulation which investigates the coupling of fast and Alfvén magnetohydrodynamic (MHD) waves in a nonuniform dipole equilibrium. This represents the time‐dependent extension of the normal mode ( ∝exp(−iωt)) analysis of Wright and Elsden (2016) and provides a theoretical basis for understanding 3‐D Alfvén resonances. Wright and Elsden (2016) show that these are fundamentally different to resonances in 1‐D and 2‐D. We demonstrate the temporal behavior of the Alfvén resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 36 publications
4
43
0
Order By: Relevance
“…The above equations are the components of the momentum and induction equations written in our curvilinear coordinates false(α,β,γfalse) and simulation variables. They are the same as in Elsden and Wright (), except that we now include a nonzero η in Ohm's Law.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above equations are the components of the momentum and induction equations written in our curvilinear coordinates false(α,β,γfalse) and simulation variables. They are the same as in Elsden and Wright (), except that we now include a nonzero η in Ohm's Law.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…In our notation this gives αmaxfalse(βfalse)=r0)(21+cosfalse(βfalse)trueα^ where r0 is the distance to the subsolar magnetopause, and the index trueα^ (simply α in Shue et al, ) controls the degree of flaring on the flanks evident in Figure 3. In the axisymmetric magnetic field employed in Elsden and Wright (, ), the edge of the staggered grid coincided with a surface αmax= const., and the only quantity needing to be defined there was Bγ (a proxy for the magnetic pressure). This corresponds to the situation in Figure a, where the red line shows the magnetopause in a surface of constant γ along with the grid points in α and β.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…The stability and accuracy of the method under these conditions is evidenced by the conservation of energy, typically to one part in 10 4 at the end of a simulation. All quantities presented in this paper are dimensionless, given that the equations being solved (see Elsden & Wright, , equations (9)–(13)) have been normalized by characteristic values: lengths by R 0 ; magnetic field by the background field B 0 = B ( α max = R 0 , β = 0, γ = 0); densities by ρ 0 = ρ ( α max = R 0 , β = 0, γ = 0); velocities by V0=B0μ0ρ0; times by t 0 = R 0 V 0 .…”
Section: Modelmentioning
confidence: 99%
“…Further, the inclusion of azimuthal magnetic and density asymmetries has also been used to consider the effect of a plasmaspheric plume on ULF wave propagation (Degeling et al, ). A key aspect of the current work is considering the excitation of FLRs in 3‐D (Elsden & Wright, , ; Wright & Elsden, ), where resonances can exist at any given polarization angle between toroidal and poloidal. Elsden and Wright () showed that the important quantity for efficient resonant excitation is the magnetic pressure gradient along the direction of polarization of the Alfvén wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation